2023
DOI: 10.1021/acs.langmuir.3c01360
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Characterization of GX-50 and Vitamin C Co-encapsulated Microcapsules by a Water-in-Oil-in-Water (W1/O/W2) Double Emulsion–Complex Coacervation Method

Ruijuan Wang,
Chunliu Ma,
Haitao Yan
et al.

Abstract: Co-encapsulated xanthoxylin (GX-50) and vitamin C (Vc) microcapsules (GX-50-Vc-M) were prepared by the combination of a water-in-oil-in-water (W1/O/W2) double emulsion with complex coacervation. The W1/O/W2 double emulsion was prepared by two-step emulsification, and it has a uniform particle size of 8.388 μm and high encapsulation efficiencies of GX-50 (85.95%) and Vc (67.35%) under optimized process conditions. Complex coacervation occurs at pHs 4.0–4.7, which has the highest encapsulation efficiency of GX-5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“…The results indicate that although the co-encapsulated L-Vc-GX-50 liposomes do not have a synergistic effect, they have higher antioxidant capacity than single encapsulated L-GX-50 or L-Vc liposomes, which are consistent with our previous research on co-encapsulated GX-50 and Vc microcapsules by a water-in-oil-in-water (W 1 /O/ W 2 ) double emulsion−complex coacervation method. 32 3.5. Determination of Tyrosinase Activity Inhibition.…”
Section: Determination Of Antioxidant Activitymentioning
confidence: 99%
See 4 more Smart Citations
“…The results indicate that although the co-encapsulated L-Vc-GX-50 liposomes do not have a synergistic effect, they have higher antioxidant capacity than single encapsulated L-GX-50 or L-Vc liposomes, which are consistent with our previous research on co-encapsulated GX-50 and Vc microcapsules by a water-in-oil-in-water (W 1 /O/ W 2 ) double emulsion−complex coacervation method. 32 3.5. Determination of Tyrosinase Activity Inhibition.…”
Section: Determination Of Antioxidant Activitymentioning
confidence: 99%
“…Therefore, it is difficult to directly apply them in cosmetic formulation. Moreover, studies have shown that co-encapsulation can improve the EE of another active ingredient, especially hydrophilic active ingredient. , Furthermore, the popular functional cosmetics often need a reasonable combination of multiple active ingredients to achieve multiple effects…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations